2021
DOI: 10.1038/s42004-021-00612-0
|View full text |Cite
|
Sign up to set email alerts
|

Intermetallic PdZn nanoparticles catalyze the continuous-flow hydrogenation of alkynols to cis-enols

Abstract: Designing highly active and stable lead-free palladium-based catalysts without introducing surfactants and stabilizers is vital for large-scale and high-efficiency manufacturing of cis-enols via continuous-flow semi-hydrogenation of alkynols. Herein, we report an intermetallic PdZn/ZnO catalyst, designed by using the coupling strategy of strong electrostatic adsorption and reactive metal-support interaction, which can be used as a credible alternative to the commercial PdAg/Al2O3 and Lindlar catalysts. Interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…These results suggest that Pd-based catalysts can easily activate H 2 and that CO adsorption is the rate-determining step during hydrogenation. Meanwhile, the kinetic isotope experiments showed a lower times (1.22–1.45) of CO hydrogenation rate under the D 2 atmosphere than that under the H 2 atmosphere (Figure S8E,F), which further indicates that the H 2 activation step is rapid and not significantly included in the rate-determining step. , Previous studies have reported that intermetallic catalysts promote selective hydrogenation, such as the CC semihydrogenation of alkynols or acetylene to form enols or olefins, , CC hydrogenation of 1,3-butadiene to 1-butene, hydrogenation of CO 2 to methanol, NO 2 hydrogenation of nitrophenols to aminophenols, and N-methylation of N -methylaniline to N , N -dimethylaniline in organic solvents or solvent-free conditions via surface geometric and electronic effects. Furthermore, reactions conducted in isopropanol and cyclohexane only generated CO hydrogenated MFA with a selectivity of 99.9%; however, the MF conversion rates were <20% (Figure S8I).…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…These results suggest that Pd-based catalysts can easily activate H 2 and that CO adsorption is the rate-determining step during hydrogenation. Meanwhile, the kinetic isotope experiments showed a lower times (1.22–1.45) of CO hydrogenation rate under the D 2 atmosphere than that under the H 2 atmosphere (Figure S8E,F), which further indicates that the H 2 activation step is rapid and not significantly included in the rate-determining step. , Previous studies have reported that intermetallic catalysts promote selective hydrogenation, such as the CC semihydrogenation of alkynols or acetylene to form enols or olefins, , CC hydrogenation of 1,3-butadiene to 1-butene, hydrogenation of CO 2 to methanol, NO 2 hydrogenation of nitrophenols to aminophenols, and N-methylation of N -methylaniline to N , N -dimethylaniline in organic solvents or solvent-free conditions via surface geometric and electronic effects. Furthermore, reactions conducted in isopropanol and cyclohexane only generated CO hydrogenated MFA with a selectivity of 99.9%; however, the MF conversion rates were <20% (Figure S8I).…”
Section: Resultsmentioning
confidence: 77%
“…Meanwhile, two obvious lattice spacings were observed at 0.231 and 0.219 nm, which were consistent with the [111] plane of Pd and PdZn nanoparticles, respectively (Figure S1D,F). , The compositions of intermetallic PdZn/ZnO were further confirmed by X-ray energy dispersive spectroscopy (EDS) mapping analysis (Figure S1G–J). High-angle annular dark-field TEM imaging of a representative particle revealed a periodic z-contrast bright–dark change, which indicated an ordered arrangement of Pd and Zn atoms, as well as the formation of highly ordered PdZn intermetallic nanoparticles (Figure B,C).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…This is confirmed by the fact that binding energy of Pd 0 has a positive shift (ca. 0.6 eV) due to strong metal-support interaction and formation of PdZn species [59]. In the case of palladium in oxidized state such shifting was not observed, confirming stabilization of PdO particles with the polymer.…”
Section: Characterization Of Catalystsmentioning
confidence: 75%
“…The selective semihydrogenation of alkynols to alkenols is of great significance in the industrial manufacture of fine and intermediate chemicals . Notably, the typical 2-methyl-3-buten-2-ol (MBE) serves as a crucial intermediate for vitamin E synthesis, with a global demand approximating 140,000 tons annually. Metallic Pd-based catalysts (Lindlar catalysts) stand out as highly efficient hydrogenation catalysts in industrial alkynol hydrogenation using hydrogen molecules as hydrogen sources. , However, the strong interaction between Pd and sp 2 carbon within the C=C bond of alkenes usually leads to undesirable overhydrogenation. Nevertheless, the pervasive use of excess hydrogen molecules imposes severe limitations on large-scale applications due to heightened safety and environmental concerns. Therefore, the pursuit of sustainable strategies is imperative to further decrease the economic and environmental footprints of the semihydrogenation process.…”
Section: Introductionmentioning
confidence: 99%